Effect of Financial Ratios on Firm Value with Profit Growth As Moderating Variable On Acquisition Companies in Indonesia - Andriyani, Ima; Azrin, Amrillah; Imam, M.Khairul (Neo Journal of economy and social humanities, 2023)
This study aims to determine and analyze the effect of financial ratios on firm value with profit growth as a moderating variable in Indonesian Acquisition Companies, both directly and indirectly. The population in this study are all Acquisition Companies listed on the Indonesia Stock Exchange during the 2018-2022 period, by taking samples using a purposive sampling method, where the determination of the sample is based on certain criteria. Based on these criteria, seven companies were sampled in this study. Data analysis used in this research is to use the Moderated Regression Analysis (MRA) method which is operated through the views 12 program. The results of this study indicate that the variable financial ratios consisting of liquidity ratios, leverage ratios, profitability ratios and activity ratios both directly and significantly influence firm value, as well as indirectly, where liquidity ratios, leverage ratios, profitability ratios and ratios activity has a significant effect on firm value through profit growth. The results of the determinant coefficient test can be interpreted that the independent variable is able to explain or is able to describe the dependent variable as a whole.